2008
DOI: 10.1016/j.febslet.2008.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of SIRT6 protein levels by nutrient availability

Abstract: Sirtuins have been shown to regulate life-span in response to nutritional availability. We show here that levels of the mammalian sirtuin, SIRT6, increased upon nutrient deprivation in cultured cells, in mice after fasting, and in rats fed a calorie-restricted diet. The increase in SIRT6 levels is due to stabilization of SIRT6 protein, and not via an increase in SIRT6 transcription. In addition, p53 positively regulates SIRT6 protein levels under standard growth conditions but has no role in the nutrient-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
133
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 19 publications
11
133
1
Order By: Relevance
“…Furthermore, SIRT6-mediated autophagy is crucial for determination of CSE-induced HBEC senescence. Consistent with recent findings regarding SIRT1, CSE reduced SIRT6 expression at the protein level without apparent changes in the amount of SIRT6 mRNA, suggesting that CSE-induced protein modification may lead to proteasomal degradation of SIRT6 (27). Although the involvement of SIRT6 in COPD pathogenesis has been proposed without detailed mechanisms (28), our findings of decreased expression levels of SIRT6 in lung homogenates from COPD patients may support the notion that reduced SIRT6 is associated with COPD development through the enhancement of cellular senescence created by insufficient autophagy during CS exposure.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, SIRT6-mediated autophagy is crucial for determination of CSE-induced HBEC senescence. Consistent with recent findings regarding SIRT1, CSE reduced SIRT6 expression at the protein level without apparent changes in the amount of SIRT6 mRNA, suggesting that CSE-induced protein modification may lead to proteasomal degradation of SIRT6 (27). Although the involvement of SIRT6 in COPD pathogenesis has been proposed without detailed mechanisms (28), our findings of decreased expression levels of SIRT6 in lung homogenates from COPD patients may support the notion that reduced SIRT6 is associated with COPD development through the enhancement of cellular senescence created by insufficient autophagy during CS exposure.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, it has been shown that SIRT6 is stabilized by nutrient deprivation and CR in cultured cells and rats, respectively [29]. While the details of the molecular interaction between SIRT6 and DNA repair are not clear, it is speculated that CR can regulate the SIRT6-mediated stability of WRN and that other sirtuins may also be implicated in this regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Drosophila dSir2 has been functionally linked to CR-dependent life span through a mechanism linked to the HDAC Rpd1 (Rogina and Helfand 2004), but C. elegans Sir-2.1 increases life span through a CR-independent mechanism linked to the IIS pathway (Tissenbaum and Guarente 2001). Nevertheless, there is no doubt that Sirtuins are functionally linked to the CR response in mammals, since CR up-regulates SirT1, SirT2, SirT3, and SirT6 and down-regulates SirT4 Shi et al 2005;Wang et al 2007;Kanfi et al 2008). In fact, recent and controversial data have suggested that CR might not induce SirT1 up-regulation, but its down-regulation in liver (Chen et al 2008a).…”
Section: The Exertion Of Sirtuinsmentioning
confidence: 99%